PENGEMBANGAN WISATA KULINER BERBASIS BAHAN PANGAN LOKAL SEBAGAI DAYA SAING DI DESA WISATA SAKERTA TIMUR KABUPATEN KUNINGAN JAWA BARAT - Sari, Ira Maya; Sembiring, Vienna Artina; Wicaksono, Haryo (Jurnal Ilmiah Pariwisata, 2019)
Culinary tourism is one of domestic and foreign tourists attractions who take a journey with the aim to enjoy various types of local food. Culinary in tourism areas also has a high that competitiveness in the context of promoting tourism in the Sakerta Timur tourism village, Kuningan, one of the ways is by developing local food-based culinary tourism. The purpose of this research is to identify local food ingredients that have potential to be developed into culinary tourism to raise the competitiveness of the Sakerta Timur tourism village. The methods of these research is used qualitative descriptive using SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) in the Sakerta Timur tourism village in July 2019. The results of this study is to the identify the local food ingredients that can be developed, so it will be competitive for culinary tourism. The local food ingredients are white mushrooms, cassava, sweet potatoes, fresh water fish, nira and coffee. Examples of product development are mushroom sauce, sweet potato sticks, pempek, palm sugar, millennial getuk rolls and coffee beans.